Bile Acid-Based Lipid Nanoparticles to Ameliorate Oral Bioavailability of Gliclazide: A Response Surface Methodology Approach - Bhavani, Muggu Sankara; Saravanan, Ravindran (Indian Journal of Pharmaceutical Education and Research, 2026)
Background/Objectives: Gliclazide is one of the commonly used oral anti-diabetic agents. It suffers limited and variable bioavailability due to poor solubility and intra- and inter-subject variability. The prime objective of this work was to upgrade its oral bioavailability via enhancing the solubility and dissolution rate by making lipid-based bile nanoparticles. Materials and Methods: Gliclazide loaded nanoparticles made up of lipids and bile salts were developed by emulsion solvent evaporation technique followed by ultrasonication. The response surface methodology was employed to optimize various formulation factors towards achieving maximum solubility of the drug with greater entrapment efficiency. Design of experiments analysis was performed to elucidate the impact of the factors on the responses. The optimized nanoparticles were characterized for particle size, dissolution rate and permeability. Results: All the formulation factors exhibited significant impact on both solubility and drug entrapment at p<0.05. The optimized nanoparticles exhibited an improvement of 30.7 times in solubility against pure drug. The optimized formulation enhanced the solubility of gliclazide to 1.32 mg/mL. The particle size of the nanoparticles from the optimized formulation resulted was 197.4 nm with PDI of 0.239. Conclusion: These results concluded that the oral bioavailability would be improved through improved solubility and dissolution rate from the lipid-based nanoparticles of gliclazide.
Keywords: Gliclazide; Solubility; Bioavailability; Lipid-based nanoparticles; Response surface; methodology